Social Burden and Economic Cost Estimation of Fatal Injuries in Workers Affiliated to Social Security in Ecuador: a Shared Challenge in Public and Occupational Health - Antonio Ramón Gómez-García; Chen Han Tsao Wu; Evelyn Nathaly Ruiz Barzola; Alywin Hacay Chang (Revista de Investigación e Innovación en Ciencias de la Salud)
Introduction. Currently, there is limited knowledge on quantifying the labour and monetary losses due to work-related fatalities in developing countries.